Pentingnya Pendidikan Agama Kristen Terhadap Moral Siswa SMP Negeri 6 Wewewa Timur Sumba Barat Daya - Desi Ernawati Lende (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Christian religious education in schools has an important role in forming students' morals. This subject not only focuses on teaching religious doctrine, but also on forming character, ethical values, and attitudes that are in accordance with Christian teachings. In the context of formal education, Christian religious education functions as a means of instilling moral values such as honesty, responsibility, love and tolerance. This research aims to analyze how the implementation of Christian Religious Education in schools can influence students' moral formation, as well as the factors that support and hinder this process. The research method used is a qualitative approach with interviews, observation and document analysis as data collection techniques. The research results show that Christian religious education delivered with a contextual approach and relevant to students' lives can have a positive impact on their moral formation. Apart from that, the involvement of teachers who have good moral integrity and creative teaching methods is a determining factor for success. Thus, Christian religious education in schools has a strategic role in creating a young generation who have morals, character, and are able to live according to Christian principles amidst the challenges of the times.